(untitled) (Scientific journal of the Fergana State University, 2023)
The study of the relation of the Turkish words in “Mahbub ul-Qulub” to the current Uzbek literary language showed that socio-political processes, scientific and technical progress, changes and updates in the economic and educational spheres taking place in the society under its influence, new words and terms appear in the vocabulary of the language, at the same time, certain lexemes become obsolete and become a historical category.Most of the Turkish words used in the article are used today. For example, Alisher Navoi used kinship, human body parts, zoonyms, time units, numbers, household, socio-political lexemes, the concept of person, and most of the words denoting character-characteristics have the same form and meaning in our literary language today. you can see that noda is used.